1001 climbing tips : the essential climbers' guide, from rock, ice and big-wall climbing to diet, training and mountain survival /: the essential climbers' guide, from rock, ice and big-wall climbing to diet, training and mountain survival. (2016) - Kirkpatrick, Andy, 1971-
No abstract available